THE EFFECT OF THE JENGA GAME ON VOCABULARY TEACHING AT AL-MARMAHAH INTEGRATED ISLAMIC ELEMENTARY SCHOOL, KAMPUNG DALAM, PARIAMAN - Nimatus - Saidah; Devy - Aisyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this discussion is to determine the effect of playing jenga on mufradat learning in Al-Marhamah Kampung Dalam Pariaman Integrated Islamic Elementary School students. And researchers used experimental research methods with three data collection instruments, namely through observation, interviews, and exams/tests. The research design is Quasi Experiment Design with Nonequivalent Control Group Design. And after the researcher used the jenga game for abstract learning, the researcher found that the results of to were greater than tt, namely 2.55 1.71 therefore Ho was rejected and Ha was accepted, meaning that there was a difference between the value of mufradat learning by using the jenga game with the value of mufradat learning without using jenga games. The conclusion from this study is that playing jenga has an effect on the value of mufradat learning in students.